Contemporary Trends of the Epidemiology, Clinical Characteristics, and Resource Utilization of Necrotizing Fasciitis in Texas: A Population-Based Cohort Study - Lavi Oud; Phillip Watkins (Critical Care Research and Practice)
Introduction. There are limited population-level reports on the contemporary trends of the epidemiology, clinical features, resource utilization, and outcomes of necrotizing fasciitis (NF). Methods. We conducted a cohort study of Texas inpatient population, identifying hospitalizations with a diagnosis of NF during the years 2001–2010. The incidence, clinical features, resource utilization, and outcomes of NF hospitalizations were examined. Results. There were 12,172 NF hospitalizations during study period, with ICU admission in 50.3%. The incidence of NF rose 2.7%/year (P=0.0001). Key changes between 2001-2002 and 2009-2010 included rising incidence of NF (5.9 versus 7.6 per 100,000 [P<0.0001]), chronic comorbidities (69.4% versus 76.7% [P<0.0001]), and development of ≥1 organ failure (28.5% versus 51.7% [P<0.0001]). Inflation-adjusted hospital charges rose 37% (P<0.0001). Hospital mortality (9.3%) remained unchanged during study period. Discharges to long-term care facilities rose from 12.2 to 30% (P<0.0001). Conclusions. The present cohort of NF is the largest reported to date. There has been increasing incidence, chronic illness, and severity of illness of NF over the past decade, with half of NF hospitalizations admitted to ICU. Hospital mortality remained unchanged, while need for long-term care rose nearly 2.5-fold among survivors, suggesting increasing residual morbidity. The sources of the observed findings require further study.